In silico evaluation of anti-colorectal cancer inhibitors by Resveratrol derivatives targeting Armadillo repeats domain of APC: molecular docking and molecular dynamics simulation - Akash, Shopnil; Islam, Md. Rezaul; Bhuiyan, Abdul Ali; Islam, Mirza Nafeul; Bayıl, Imren; Saleem, Rasha Mohammed; Albadrani, Ghadeer M.; Al-Ghadi, Muath Q.; Abdel-Daim, Mohamed M. (Frontiers in Oncology, 2024)
Colorectal cancer is the second leading cause of cancer-related deaths. In 2018, there were an esti-mated 1.8 million cases, and this number is projected to increase to 2.2 million by 2030. Despite its prevalence, the current therapeutic option has a lot of side effects and limitations. Therefore, this study was designed to employ a computational approach for the identification of anti-cancer inhib-itors against colorectal cancer using Resveratrol derivatives. Initially, the pass prediction spectrum of 50 derivatives was conducted and selected top seven compounds based on the maximum pass pre-diction score. After that, a comprehensive analysis, including Lipinski Rule, pharmacokinetics, ADMET profile study, molecular orbitals analysis, molecular docking, molecular dynamic simula-tions, and MM-PBSA binding free energy calculations. The reported binding affinity ranges of Resveratrol derivatives from molecular docking were -6.1 kcal/mol to -7.9 kcal/mol against the tar-geted receptor of human armadillo repeats domain of APC (PDB ID: 3NMW). Specifically, our findings reported that two compounds [(03) Resveratrol 3-beta-mono-D-glucoside, and (29) Resveratrol 3-Glucoside] displayed the highest level of effectiveness compared to all other deriva-tives (-7.7 kcal/mol and -7.9 kcal/mol), and favorable drug-likeness, and exceptional safety profiles. Importantly, almost all the molecules were reported as free from toxic effects. Subsequently, mo-lecular dynamic simulations conducted over 100ns confirmed the stability of the top two lig-and-protein complexes. These findings suggest that Resveratrol derivatives may be effective drug candidate to manage the colorectal cancer. However, further experimental research, such as in vitro/in vivo studies, is essential to validate these computational findings and confirm their practical value.